DIGITAL TECHNOLOGY AND THE NEW DIRECTION IN HISTORY TEACHING AND RESEARCH IN THE NIGERIA’S TERTIARY INSTITUTIONS IN THE 21ST CENTURY - Adesote Samson Adesola; Tella Olumuyiwa Abidemi; James Omolola Bimpe (International Journal of Educational Review, 2026)
This paper recognises that recent advances in digital technologies have provided unprecedented opportunities for effective teaching and research in various fields of human endeavour. While majority of scholars in different tertiary institutions, most especially in the developed countries have turned increasingly to using and exploring information technologies as scholarly tools for teaching and research, they are yet to be fully employed by many Nigerian academics. Adequate knowledge of some fundamental skills provided by digital technology such as the development of tools for critical analysis and the ability to synthesise materials and bring together different methodologies to solve complex problems are significant in competing favourably in the 21st century world of scholarship. It is on this premise that this paper argues that rather than seeing digital technologies as representation for an abandonment of what the discipline of history is meant to stand for as posited by the traditionalists, it is a justification for saving the discipline from the insularities of its traditionalism. In other words, the adoption of digital technology in history teaching and research is not a replacement or rejection of traditional historical inquiry, but an extension of the traditional scope of history. Thus, the main thrust of this paper is the re-conceptualisation of historical scholarship in the age of information technology. The paper identifies inadequate infrastructure, limited internet access, unreliable power supply, high cost of digital devices and software among others as major challenges militating against the effective integration of digital technology into teaching and research in most Nigerian tertiary institutions. It concludes that the exploration of the spaces of engagement through interdisciplinary, collaborative and technological research helps to invigorate and accelerate the transformation of historical scholarship and the production of knowledge in history in the 21st century. The methodology adopted in this paper is historical, thematic and analytical, utilising materials from primary and secondary sources.